Penanggulangan Kemiskinan: Kebijakan dalam Perspektif Gerakan Sosial - J. Nasikun (Jurnal Ilmu Sosial dan Ilmu Politik, 2002)
The poors have been ignored within the process of economic development, as myth of non-existence reveals. More over, they have been discredited as the attempt to recognise their existence become a liability. It is widely assumed that policies in favour to the poor essentially compromising the interest of the growing economy. Based on this kind of "auto-critics" the author advocates the importance of integrating the poor within the entire national system of development. Not only the policies have provided the poor with sufficient access to information and technology and the market, a fair distribution of resourcess is imperative. Simply put, the thrust of poverty aleviation policy is restructuring the economy so that the poors gain wider access and stronger bargaining power. In order to make this imperative, poverty aleviation should be treated as social movement. By approaching poverty aleviation as a form of social movement, social and institutional bases for involving the poor in the process of development is strengthened. Moreover, the deepening of the movement eventually institutionalising the policy and the public agenda, not merely issue to be disscused by government official and a limited number of intellectuals.